SIGNIFICANCE OF CERTIFICATION OF TESTING INSTRUMENTS IN QUALITY PRODUCT MANUFACTURING (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This statement emphasizes the significance of conducting tests in the manufacturing process to ensure the production of high-quality products within enterprises. The need for testing arises as it forms the foundation for the core function of producing and utilizing equipment during the manufacturing process. Testing is crucial during production, in establishing the inventory of equipment, in the contemporary creation of testing equipment, and in the development of specific and governmental programs. The certification of testing equipment holds paramount importance, with its primary objectives being the precise documentation of equipment specifications, their compatibility with documented references, and the determination of their suitability for utilization.